The first study of reference intervals for blood biochemistry of healthy pet Pacific parrotlets (Forpus coelestis) in Thailand. (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study aimed to establish baseline biochemical reference values for apparently healthy Pacific parrotlets in Thailand. Materials and Methods: Blood samples were obtained from 30 healthy individuals, and analyses were conducted using the VETSCAN® VS2 with Avian/Reptilian Profile Plus rotors. Results: The results showed the measured biochemical parameters with the reference intervals included aspartate aminotransferase (73–274 U/L), glucose (235–324 mg/dl), total protein (2–3.3 gm/dl), albumin (1.5–2.5 gm/dl), globulin (0.1–1.2 gm/dl), phosphorus (1.2–5 mg/dl), calcium (7.9–9.7 mg/dl), sodium (147–157 μmol/l), potassium (2.2–3.8 μmol/l), bile acids (0–34 μmol/l), creatine kinase (44–543 U/L), uric acid (1.4–9.7 mg/dl), plasma protein (3–5 gm/dl), and packed cell volume (49%–55%). Conclusion: This study offers the first reference biochemistry values specific to Pacific parrotlets in Thailand, contributing to improved veterinary clinical practices, accurate diagnosis, and effective care for this species.J. Adv. Vet. Anim. Res., 12(2): 344–349, June 2025http://doi.org/10.5455/javar.2025.l902